The management of auricular defect using retroauricular flap - Roosseno, Ratna Rayeni Natasha; ., Primawati (International Journal of Research in Medical Sciences, 2020)
Management of auricular defect is still a challenge for reconstructive plastic surgeons. The complexity of anatomy and shape will make the reconstruction complicated. It is also inevitable that choosing the right donor to close the defect that resembles the original contour is one of the success indicators of any ear reconstruction. There are wide selections of techniques for the management of auricular defect. Retroauricular flap is one of the best choices in auricular reconstruction due to its vascular richness, low of failure rate, similarity of tissue contour and the ease of closing the donor-site defect primarily. This article reported three cases of auricular defect with various causes: crushed injury, human bite, and tumor excision. Two stages of surgeries were performed on all three patients. After sufficient debridement, the ear defect is planted beneath retroauriculomastoid dermis. The second stage, three weeks from the first surgery, the donor flap is separated from it host. One week follow up after the second stage surgery, all of the post-operative wounds showed no signs of infection, minimal scar formation and has satisfied aesthetic outcomes. The retroauricular flap has the advantages of simple dissection, low failure rate and has a good shape, texture, color for a very good aesthetic results. This flap may be considered as a good solution in the management of auricular defect and a flap bank for ear reconstruction.